Improvement of water and nutrient efficiencies oil palm through bio-silicic acid application - Laksmita Prima SANTI; Adhy ARDIYANTO; Agung KURNIAWAN; Lilik A PRABOWO; Ian SEBASTIAN (E-Journal Menara Perkebunan, 2021)
Crop water use efficiency is critical for high yields in conditions of limited water supplies. This study aims at determining the effect of application bio-silicic acid (BioSilAc) on water use efficiency and nutrient availability for immature (2 years after planting) and mature (5 years after planting) oil palms in sandy soil during a period of low rainfall. A field experiment was conducted on sandy soil at an oil palm plantation in Central Kalimantan. The experiment was arranged in a randomized block design with seven treatments and three replicates using a combination of composted empty fruit bunches of oil palm (CEFBOP) and BioSilAc applications. The treatments (tree-1 year-1) were as follows (tree-1 year-1): (T1) 100% NPK standard dosage; (T2) T1 + 1.5 kg quartz sand; (T3) 75% (T1) + 1.5 kg quartz sand; (T4) T1+ 4 tablets BioSilAc; (T5) 75% (T1) + 4 tablets BioSilAc; (T6) T1 + 50 kg CEFBOP + 2 tablets BioSilAc; and (T7) 75% (T1) + 50 kg CEFBOP + 2 tablets BioSilAc. The parameters observed were soil and leaf nutrient contents, average weight, and number of fresh fruit bunch (FFB), and daily water usage and water potential using a sap flow meter and stem psychrometer to calculate water use efficiency in T1 (control) and T5 which represents the application of BioSilAc. The results indicated that the application of 75-100% NPK + 4 tablets BioSilAc tree-1 year-1 in mature oil palm was capable of improving yield of11.9% (T5) and 12.1% (T4) and water use efficiency of 31.3% (mature) and 50.4% (immature) of the control treatment.